Sosialisasi al-Qur’an Digital Berbasis Isyarat Bagi PDSRW di Institut Tahfiz Bintulu (ITB) Sarawak, Malaysia: Pengabdian - Rakhman, Itmam Aulia; Janah, Miftahul; Mubarok, Zaki; Koidin, Mohammad (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This community service initiative is entitled "Socialization of Sign-Based Digital Qur'an for Persons with Speech and Hearing Disabilities (Penyandang Disabilitas Rungu Wicara/PDSRW) at the Institut Tahfiz Bintulu (ITB) Sarawak, Malaysia". The main objective of the program is to enhance the accessibility of Qur'anic education for PDSRW by utilizing digital technology and an inclusive education approach, while simultaneously improving the instructors' capacity to handle students with special needs. The scope of the activity includes intensive training for ITB instructors on using the Android version of the Qur'an Kemenag application and inclusive learning methods. The implementation method used the Asset-Based Community Development (ABCD) approach, focusing on empowering local assets, and was carried out through four main stages: asset identification and mapping, mobilization of community assets, practical training and mentoring, and evaluation and sustainability planning. The results showed a significant improvement in instructor capacity, with 100% of participants understanding the concept of inclusive education and 93% able to use the Qur'an Kemenag application effectively. The formation of an inclusive learning module and a plan for continuous training are indicators of the program's success. It is concluded that the ABCD approach is effective in creating a sustainable, inclusive education ecosystem.